Synthesis and In Silico Study of Multifunctional Arylthio-Tetrafluorobenzene-Imidazole Triad Compounds - Vaskina, Nailya F.; Nikiforov, Egor A.; Moseev, Timofey D.; Varaksin, Mikhail V.; Butorin, Ilya I.; Charushin, Valery; Chupakhin, Oleg N. (Synthesis, 2025)
An original, transition metal-free, two-step synthetic strategy based on sequential SNH and SNAr reactions, namely C–H functionalization of nonaromatic 2H-imidazole 1-oxide with pentafluorophenyl lithium followed by aromatic fluorine substitution with arylthioles, was proposed. A series of new arylthio-tetrafluorobenzene-imidazole triad multifunctional compounds were prepared in good yields of 62–94%. The in silico study of the synthesized triads toward biotargets associated with endothelial dysfunction (PDE5a); cancer (EGFR, CDK2); and SARS-CoV-2 viral infection (Mpro) revealed that biotarget binding selectivity was highly sensitive to the positioning of substituents on the aromatic ring. The synthesized triads could be considered as perspective lead compounds in the design of agents for pharmaceutical applications.
Keywords: Imidazole; Arylthiol; Fluoroarene; Multifunctional compounds; Nucleophilic substitution